2006
DOI: 10.1007/s10038-006-0396-3
|View full text |Cite
|
Sign up to set email alerts
|

Six novel mutations detected in the GALC gene in 17 Japanese patients with Krabbe disease, and new genotype–phenotype correlation

Abstract: Krabbe disease is an autosomal recessive leukodystrophy. It is pathologically characterized by demyelination of the central and peripheral nervous systems and the accumulation of globoid cells in brain white matter. It is caused by a deficiency of galactocerebrosidase (GALC) activity. We investigated mutations of the GALC gene in 17 Japanese patients with Krabbe disease, the largest subject number of Japanese patients to date, and found 27 mutations. Of these mutations, six were novel, including two nonsense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 14 publications
2
65
0
Order By: Relevance
“…In the lysosome, GALC catabolizes galactolipids, such as galactosylceramide and psychosine (Suzuki, 2004). Because clinical laboratories use total cell lysates from blood cells or skin fibroblasts to measure GALC activity, it is possible that GALC present in other subcellular organelles could falsely skew the enzymatic activity measured in total cells after lysis but would not reflect the useful activity of GALC in vivo in the lysosome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the lysosome, GALC catabolizes galactolipids, such as galactosylceramide and psychosine (Suzuki, 2004). Because clinical laboratories use total cell lysates from blood cells or skin fibroblasts to measure GALC activity, it is possible that GALC present in other subcellular organelles could falsely skew the enzymatic activity measured in total cells after lysis but would not reflect the useful activity of GALC in vivo in the lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations are numbered according to HGVS, which have elsewhere been described as G41S, D528N, and L618S, respectively. G57S is responsible for the majority of later-onset GLD in the Catania region of Italy (Lissens et al, 2007), D544N is found in the infantile-onset Muslim Arab population of Israel , and L634S is a prominent later-onset mutation in Japan (Xu et al, 2006;Hossain et al, 2014). All of these mutations are sometimes found in homozygosity among GLD patients, and in the homozygous state they cause later-or infantile-onset GLD respectively, suggesting they are clearly associated with the age of onset of GLD.…”
Section: Additional Later-onset Galc Mutations Also Retain Partial Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional studies would be necessary to determine whether p.V320M and others (such as p.D94=) are indeed pseudodeficiency alleles. p.L618S was found in cis with several other variants in our population (Supplementary Table S3 online), and those who carried two copies of p.L618S were categorized as being at high (1; case 9, 3,28,29,32 Nearly all of the 348 infants referred carried at least one of the three common activity-attenuating polymorphisms (p.R168C, p.D232N, p.I546T). The frequency of each was elevated in the referral population compared with published data.…”
Section: Genotypes and Phenotypesmentioning
confidence: 99%
“…Another example, p.Leu634Ser (legacy p.Leu618Ser) is primarily found in infants with Japanese ethnicity. Infants homozygous for these variants have been assigned to the high risk category, but in the literature there are only two cases of individuals homozygous for p.Leu634Ser, and both patients were adults when diagnosed with KD [41]. There are no known cases of Krabbe disease homozygous for p.Tyr319Cys.…”
Section: Second-tier Molecular Testingmentioning
confidence: 99%